PENERAPAN MODEL PEMBELAJARAN TWO STAY TWO STRAY PADA PEMBELAJARAN PERSAMAAN LINEAR DUA VARIABEL SISWA KELAS 8 SMP N 3 MOTOLING TIMUR - Tewu, Vernando; Sumarauw, Sylvia Jane Annatje; Wenas, John R (LPPM Universitas Bina Bangsa, 2024)
The two stay two stray learning model is a cooperative learning model that provides opportunities for groups to share knowledge and learning experiences with other groups, where in the group there are group members who stay to share the material obtained and group members who visit other groups to find information about the material obtained in the group. This study was conducted to determine whether using the two stay two stray learning model can improve student learning outcomes, especially in the material of Two Variable Linear Equations. The posttest type experimental design used in this study was posttest only control group design. The sampling technique is simple random sampling (simple random technique). The subjects in this study were class VIIIB students as an experimental class consisting of 22 students and class VIII A students as a control class consisting of 22 students at SMP Negeri 3 Motoling Timur, these two classes were randomly selected. Data were obtained from the learning outcomes of experimental and control class students. With the average learning outcomes of experimental class students 81.046 and the average learning outcomes of control class students 71.27. The data normality test is fulfilled so that the data is normally distributed. In the results of data analysis with a real level of 0.05 obtained 0.100 in the experimental class and 0.999 in the control class. Also obtained the result that the variance is homogeneous